Cognitive-Behavioral Divergence Is Greater Across Alternative Male Reproductive Phenotypes Than Between the Sexes in a Wild Wrasse - Cummings, Molly E.; Marsh-Rollo, Susan E.; Alonzo, Suzanne H. (Frontiers in Ecology and Evolution, 2022)
Sexual selection is a powerful diversifier of phenotype, behavior and cognition. Here we compare cognitive-behavioral traits across four reproductive phenotypes (females and three alternative males) of wild-caught ocellated wrasse (Symphodus ocellatus). Both sex and alternative male phenotypes are environmentally determined with sex determination occuring within the first year, and males transition between alternative phenotypes across two years (sneaker to satellite or satellite to nesting). We captured 151 ocellated wrasse and tested them on different behavior and cognition assays (scototaxis, shoaling, and two detour-reaching tasks). We found greater divergence across alternative male reproductive phenotypes than differences between the sexes in behavior, problem-solving, and relationships between these traits. Nesting males were significantly less bold than others, while sneaker males were faster problem-solvers and the only phenotype to display a cognitive-behavioral syndrome (significant correlation between boldness and problem-solving speed). Combining these results with prior measurements of sex steroid and stress hormone across males, suggests that nesting and sneaker males represent different coping styles. Our data suggests that transitioning between alternative male phenotypes requires more than changes in physiology (size and ornamentation) and mating tactic (sneaking versus cooperation), but also involves significant shifts in cognitive-behavioral and coping style plasticity.